L’apparent paradoxe de la notoriété actuelle de Karl Polanyi - Servet, Jean-Michel (Revue Francaise de Socio-Economie, 2018)
Pour qui est convaincu qu’un auteur n’a rien d’un esprit tombé du ciel et qu’un écrit particulier ne peut être produit dans n’importe quelles conditions, comme pour qui pense que son biographe doit absorber les conditions économiques, sociales, politiques, morales et intellectuelles spécifiques de sa vie, ses racines familiales, ses réseaux de proches et d’amis, ses collaborations professionnelles, les débats scientifiques auxquels il a participé et jusqu’à ses traits psychologiques et somatiques, Karl Polanyi. A life on the left, la biographie que Gareth Dale, senior lecturer à la Brunel University de Londres, a consacrée à l’auteur de La Grande Transformation, peut être considérée comme un modèle. Elle remplit en effet largement l’objectif qu’il se donne : « met[tre] l’accent sur le processus de formation intellectuelle de Polanyi, car il a interagi avec l’environnement social et géopolitique changeant », et elle a été en cela largement saluée par ceux et celles qui en ont rendu compte. À la différence d’autres travaux moins bien documentés car réalisés par des biographes ignorant le hongrois et l’allemand et réduits à une documentation essentiellement en langue anglaise, les compétences linguistiques (pour ce qui est de l’allemand) associées à une subvention lui permettant de disposer de la traduction de textes en hongrois ou de leurs résumés, de ce spécialiste de l’œuvre de Polanyi et plus généralement des rapports internationaux et politiques de l’époque où ce dernier a vécu lui ont permis de saisir avec finesse le contexte global et personnel de Polanyi…
Sociology
Keywords: Karl Polanyi: A Life on the Left (Book); book review

Embeddedness and Effervescence: Political Economy and Community Sociality through a Century of Transformations in Rural Hungary - Hann, Chris (Ethnologie française, 2017)
S’appuyant sur un travail de terrain de longue haleine dans un village de la grande plaine hongroise, l’auteur analyse les liens entre économie politique et formes de sociabilité communément englobées sous le terme de rituel. Trois cycles d’intégration et de désintégration sont décrits. Chacune des phases de déstructuration a conduit à de nouvelles formes d’« auto‑protection » (Karl Polanyi) et à la construction de nouvelles relations communautaires. Les formes exemplaires de sociabilité aujourd’hui sont sensiblement différentes de celles de l’ère socialiste.
Anthropology
Keywords: (post)socialisme; Populisme; Rituel; anthropologie économique; economic anthropology; embeddedness; populism; post-socialism; ritual

Karl Polanyi. Remettre l'économie à sa place - Behrent, Michael C. (Sciences humaines, 2016)
History

La « marchandisation » croissante du monde - Dupuis, Flavien (Esprit, 2016)
Un examen de la « marchandisation » montre qu’elle s’accompagne d’un processus inverse de dé-marchandisation, en particulier du travail, des ressources naturelles, du corps et des échanges, sous l’impulsion de l’État-Providence, du droit et de la société civile. ENG: "Commodification" is accompanied by the opposite movement of de-commodification, in particular for labor, natural ressources, bodies and exchanges, under the impulse of the Welfare state, law and civil society.
Economics
Keywords: commodification; decommodification

État social, démocratie et construction européenne. Pour une citoyenneté sociale européenne - Delruelle, Édouard (Revue Française d'Histoire des Idées Politiques, 2016)
L’idée de « modèle social européen » n’est-elle qu’un leurre ou un objectif politique que les forces progressistes doivent continuer à promouvoir ? L’article s’interroge sur les fondements proprement philosophiques (souvent négligés) de l’État social – à la fois système assurantiel universel et institution d’un « citoyenneté sociale » (T.H. Marshall), dont la dynamique excède la forme de l’Etat-nation., Is the idea of a “European social model” but a decoy or is it a political aim that progressive forces need to keep on promote? This paper is concerned with the (often neglected) philosophical foundations of the welfare state – both a universal insurance system and the establishment of a “social citizenship” (T.H. Marshall) whose dynamics extend beyond the form of the nation-state.
Philosophy
Keywords: social citizenship; welfare state

Cultural studies, production et économie morale - Hesmondhalgh, David; Morin, Céline (Réseaux, 2015)
Les approches issues des cultural studies ont insufflé à la recherche sur les productions médiatiques et culturelles une vigueur nouvelle et nécessaire. Cependant, il devient de plus en plus clair au fil des ans qu’elles rencontrent également de sérieuses limites. L’évaluation menée dans cet article repose sur une première partie dans laquelle nous explorons, en profitant du recul historique, la période d’opposition entre les cultural studies et l’économie politique des années 1990, en distinguant ce que nous appelons les modes théorique et populiste des cultural studies. Nous esquissons ensuite les trois « écoles » des approches cultural studies vis-à-vis de la production et de l’économie : cultural economy, production studies, et creative industries analysis. Selon nous, ces approches en cultural studies de la production et de l’industrie dans le domaine de la culture pêchent, tant dans leur mode populiste que dans leur mode théorique, par le manque d’attention portée à des problématiques fondamentales liées à la normativité dans les rapports entre la culture, les médias et l’économie. Dans les deux dernières parties, portant sur le tournant du cultural labour et le concept d’économie morale, nous suggèrerons des solutions pour une prise en compte plus explicite des problèmes de normativité, proposant ainsi une base éthique potentiellement plus rigoureuse pour l’étude de questions importantes dans le champ de la production culturelle. Nous appliquerons succinctement ce système au rapport problématique entre les biens culturels et le bien-être dans les sociétés modernes., ENG: Cultural studies approaches have provided a welcome reinvigoration of research on media and cultural production. But, as the years go by, it becomes clearer that they also suffer from important limitations. To provide a basis for the assessment in this article, the first section revisits the 1990s moment of ‘political economy versus cultural studies’ with the benefit of hindsight, distinguishing what I call the theoretical and populist modes of cultural studies. I then outline three ‘schools’ of cultural studies approaches to production and economy : cultural economy, production studies, and creative industries analysis. My argument is that, in both its theoretical and populist modes, these cultural studies approaches to production and industry in the realm of culture suffer from a lack of attention to fundamental normative issues regarding the relationship between culture, media and economy. In the final two sections, which discuss the turn to cultural labour and the concept of moral economy, I offer suggestions for how key normative issues might be addressed in a more explicit way, potentially offering a more rigorous ethical grounding for important questions regarding the realm of cultural production. I briefly apply this to the problematic relationship between cultural goods and well-being in modern societies.
Communication; Media Studies
Keywords: cultural production; cultural studies; industry; moral economy

Internet, une société contre l’État ? - Loveluck, Benjamin (Réseaux, 2015)
L’informatique en réseau a souvent été présentée comme un instrument favorisant l’auto-organisation de la société civile, à partir de modes alternatifs de distribution du pouvoir et de coordination des activités. L’histoire d’internet, abordée du point de vue de l’histoire des idées, montre que de telles propriétés ont donné lieu à la formation d’une véritable philosophie politique que nous avons appelée le libéralisme informationnel. Celle-ci a vu différents modèles d’économie politique s’affronter ; nous en présentons ici le mouvement général ainsi que les divergences internes. Nous terminons par un exposé de trois grandes formes de gouvernementalité qui en sont issues, et qui ouvrent à une critique de l’économie politique en régime numérique : la captation, la dissémination et l’auto-institution., Network computing has often been presented as an instrument promoting self-organization within civil society, through alternative modes of power distribution and coordination of activities. The history of the Internet, considered from the perspective of the history of ideas, shows that these properties have led to the formation of a genuine political philosophy that we have called informational liberalism. This article presents its overall movement and internal divisions, understood as alternative models of political economy. Finally, three main forms of governmentality stemming from this framework are identified, which pave the way for a critique of political economy in a digital regime : capturing, dissemination and self-institution.
Cultural Studies
Keywords: information society; informational liberalism; internet

Cultures régionales et développement économique dans l'espace rhénan et au-delà - Kahn, René (Revue d'Allemagne et des Pays de Langue Allemande, 2015)
Contemporary economic thought is overwhelmingly dominated by the dogma of the neoclassical school and the Austrian neoliberal school, according to which social organization can fully be understood from two hypotheses: the society can be reduced to its economic aspects, and economic activities are exclusively explained by the utilitarist rationality of individuals. This approach makes unnecessary, at least in the economic sphere, the construction of a collective cultural framework based on preferences and values specific of a "situated" community. Now, many multidisciplinary works confirm the validity of Karl Polanyi's observations and the embedment of cultural aspects in the economic activity, especially within the firms and the territories. This paper discusses the contributions of two collective works: the first book devoted to the Rhine area's model of firm; the second devoted to the relationships between regional cultures and economic development. Based on the literature on this subject, the paper questions the nature of such a model. It also shows how regional cultures succeed to enrich the economic sphere, beyond the methodological individualism, through the construction of a culture of development. (English)
Area Studies
Keywords: Germany; economic theory; embeddedness

Les paiements pour services environnementaux de la Fondation Natura Bolivia entre logiques réciprocitaires, redistributives et marchandes, - Bétrisey, Florence; Mager, Christophe (Revue Française de Socio-Économie, 2015)
La diffusion internationale des paiements pour services environnementaux (PSE) a été interprétée en 2010 par le gouvernement bolivien d’Evo Morales comme une réponse strictement néolibérale à la nécessité d’assurer une gestion durable des ressources naturelles. Supposée amener à terme à l’éviction de toute régulation autre que marchande – qu’elle s’applique à la nature ou aux rapports entre personnes –, la mise en place de PSE n’a pas été encouragée par les autorités nationales boliviennes. Des projets de PSE ont toutefois été lancés, dont les Acuerdos Reciprocos por el Agua (ARA), issus d’un partenariat public-privé dans le département de Santa Cruz. En analysant leur conception et leur fonctionnement au prisme du référentiel polanyien, nous montrons que, contrairement aux craintes gouvernementales, ces PSE ne font pas abstraction des logiques organisationnelles réciprocitaires et redistributives, ajustant au contexte local un objet global., ENG: The international dissemination of payments for ecosystem services (PES) has been interpreted in 2010 by the Bolivian government of Evo Morales as a strictly neo-liberal response to the need to ensure a sustainable management of natural resources. Supposed to contribute to the crowding-out of any other regulation than market – applied to the nature or the relationship between people – the implementation of PES was not encouraged by the Bolivian national authorities. However some PES projects stemming from a public-private partnership have been initiated at local level, as the Acuerdos Reciprocos por el Agua (ARA), in the department of Santa Cruz. Analysing their design and operating through the Polanyian framework, we show that, contrary to the government fears, these PES do not ignore the reciprocal and redistributive organisational logics, adjusting a global object to the local context.
Geography
Keywords: Bolivia; Bolivie; Polanyi; hybridity; hybridité; logique marchande; market logic; paiements pour services environnementaux; payments for ecosystem services; reciprocity; redistribution; réciprocité; sustainable management

Karl Polanyi et l’encastrement politique de l’économie : pour une analyse systémique des rapports changeants entre économie et société, Karl Polanyi and political embeddedness of economy: a systemic analysis of the changing relationships between economy and society - Chochoy, Nicolas (Revue Française de Socio-Économie, 2015)
Cette contribution défend la thèse selon laquelle une interprétation fidèle de l’encastrement au sens de Karl Polanyi nécessite une analyse qui se positionne dans la relation existante entre l’économie et l’institution organisatrice du social. Cette proposition s’étaye sur une analyse systémique des rapports changeants entre économie et société qui éclaire le désencastrement comme processus d’extériorisation du Marché imaginaire autorégulateur. Face à ce processus, l’enjeu d’une économie solidaire nous semble être de créer les conditions d’une réelle auto-organisation démocratique., This paper defends the idea that a faithful interpretation of Karl Polanyi’s embeddedness requires an analysis at the level of the relationships between economy and the institution which organises the social. This proposal is based on a systemic analysis of the changing relationships between economy and society that considers the disembeddedness as an externalisation process of imaginary self-regulating market. In front of this process, the issue of solidarity economy seems to be the creation of conditions for a real democratic self-organisation.
Economics
Keywords: autotranscendance; democracy; démocratie; embeddedness; encastrement; marché; markets; solidarity economy; économie solidaire

La pluralité des logiques d’action de la Banque Palmas au Brésil : entre développement local et partenariats au niveau national, The plurality of Banco Palmas’ strategies: between local development and partnerships at a national level - Meyer, Camille (Revue Française de Socio-Économie, 2015)
Actives dans plus de 100 communautés au Brésil, les banques communautaires de développement représentent un phénomène majeur de l’économie solidaire brésilienne. En se référant aux apports théoriques de Karl Polanyi, cet article propose une analyse des logiques d’action plurielles de la première banque communautaire de développement brésilienne, la Banque Palmas., Effective in more than 100 communities in Brazil, community development banks are a major phenomenon of Brazilian solidarity economy. Referring to the theoretical contributions of Karl Polanyi, this paper proposes an analysis of the plural organizational logics of the first Brazilian community development bank, Banco Palmas.
Economics
Keywords: Brésil; banque communautaire de développement; finances solidaires; social economy; économie plurielle

Le syndicat chinois: Une institution au coeur du rapport salarial. (The Chinese Trade-Union: A Core Institution of the Wage-Earning Relationship. With English summary.) - Perisse, Muriel (Mondes en Developpement, 2015)
The official Chinese Trade Union has gained strength during the reforms, to the point that it must be considered as a central institution of the contemporary Chinese wage ratio. As a quasi-governmental organization, it belongs to the evolutionary institutional design and must find new solutions to the labor problems resulting from the reforms. However, its creativity only produces organizational solutions that are far from achieving a real counter-movement in a Polanyian sense.
Economics
Keywords: countermovement; economic development: human resources; economic integration; human development; income distribution; industry studies; international linkages to development; migration; population; role of international organizations; socialist institutions and their transitions: international trade; finance; investment; relations; and aid P33; socialist systems and transitional economies: factor and product markets; wage differentials; wage level and structure

Socioéconomie et démocratie – l'actualité de Karl Polanyi Isabelle Hillenkamp & Jean-Louis Laville (éd.) - Maucourant, Jérôme (Revue de philosophie économique, 2014)
A book review in a French journal
Economics
Keywords: book review; economic philosophy

Maintenir l'ordre économique, Maintaining the economic order - Gayon, Vincent; Lemoine, Benjamin (Politix, 2014)
La sociologie des politiques économiques défendue dans cet article prend pour objet le travail permanent de construction, de naturalisation et de maintien de l’ordre économique déployé par une multitude d’acteurs et d’instruments techniques. Il s’agit d’ouvrir des enquêtes sur la façon dont prennent forme les processus de désencastrement et de réencastrement de l’économie vis-à-vis des institutions politiques et sociales. Cette piste est suivie en quatre temps. D’abord en soulignant la portée sociogénétique de l’œuvre de Karl Polanyi et son insistance sur l’émancipation disputée et incertaine des pratiques de production et d’échange à l’égard des tutelles traditionnelles. Puis en montrant comment l’invention de l’économie en tant que sphère d’activité autonome suscite foule de résistances et de « mondes économiques renversés », opposant leurs propres normes aux « lois » supposées de l’économie. La configuration de l’après Seconde Guerre mondiale est revisitée comme un laboratoire exemplaire de réencastrement politico-étatique de l’économie. Le désencastrement néolibéral des marchés financiers à l’échelle internationale recompose ensuite les comptes de la puissance publique et privée. Ces ordres économiques balisent simultanément des zones d’accès et, réciproquement, de non-droit à la discussion publique et politique., ENG: The sociology of economic policies argued in this article investigates the permanent work of construction, naturalization and maintenance of the economic order made by a multitude of actors and technical instruments. It consists in describing how the doctrinal project of economy disembeddedness takes shape, detaching itself from the political and social institutions. This program is developed through four steps. First, by offering a constructivist reading of Karl Polanyi writings and highlighting the author’s insistence on the uncertain and contested process of production and exchanges’ practices emancipation vis-à-vis traditional guardianship. Then, by showing how the invention of the economy as an autonomous sphere of activity raises crowd resistance and « reversed economic worlds » settling their own standards and laws by opposition to the economy « rules » and values. The after World War Two configuration is revisited as an exemplary laboratory of Politics and State re-embeddedness of the economy. Then, neoliberal disembeddedness of global capital markets reshapes accounts of public and private powers. These economic orders simultaneously mark out areas of access to and, conversely, of non-entitlement to public and political discussion.
Sociology
Keywords: constructivist; embeddedness

Cartographie des échanges - Steiner, Philippe (Nouvelles Perspectives en Sciences Sociales, 2014)
In this article, I examine the main typologies of transaction that have been built from Auguste Comte to Karl Polanyi, Marcel Mauss, and Philippe Descola. Then, I suggest to reconsidering Polanyi's typology, the most common in contemporary economic sociology, and to limit the time span to modern societies. Accordingly, it is possible to map seven forms of transaction and the related institutions at work in our societies. In conclusion, the political consequences of the existence of these different forms of transaction are highlighted. (English)
Sociology
Keywords: don; exchange; gift; héritage; inheritance; marché; market; solidarity; solidarité; échange

Le don fondateur du lien social, le cas de l'économie de marché - Lasida, Elena (Transversalités, 2014)
Le don et l’échange marchand sont généralement opposés. Pourtant, l’un et l’autre apparaissent comme fondateurs du lien social dans la mesure où l’on prend en compte la relation qu’ils créent au niveau interindividuel et collectif. Le don apparaît ainsi associé à une certaine forme de réciprocité et le marché à une certaine forme de gratuité., Gift and commodity exchange are generally opposed. But both appear as founders of the social bond when we consider the relationship they create between people and in society. The gift is thus associated with some form of reciprocity and the market with some form of gratuitousness.
Sociology; Economics
Keywords: don; lien social; marché; relation; réciprocité; valeur; économie; économie sociale et solidaire

Reflections on the civil war in the period of the ideologies (1929-1939). Carl Schmitt and Karl Polanyi - Visone, Tommaso (Giornale di Storia Costituzionale, 2014)
The aim of this paper is to discuss the concept of civil war during the Thirties (1929-1939). To this purpose, the work analyses the development of the Civil War discourse in the thought of Carl Schmitt and Karl Polanyi, trying to focalize on the relationship between its consequences on the civil war and the conflicting ideologies which characterised that period. Hence, the Civil war is described, through these different narrations, showing two different sides of modernity: the destructive and dangerous one on the one hand, and the transformative and soteriological on the other.
Political Science
Keywords: 1930s; SCHMITT; Carl; civil war; ideology

Karl Polanyi - Le père de la socioéconomie - Journet, Nicolas (Les Grands Dossiers des Sciences Humaines, 2013)
Penseur au parcours très singulier, Karl Polanyi est l’un des fondateurs d’une discipline nouvelle, l’anthropologie économique, qui se consacre à l’étude des échanges dans les sociétés anciennes et ambitionne de théoriser, à l’échelle de l’humanité, ce qu’il en est des rapports entre société et économie.?Pourtant, son œuvre la plus célèbre, La Grande Transformation, ne sort pas du cadre de l’histoire... Plan of the article: Radical liberalism versus social life The free market: an intolerant doctrine An argument against neoclassical orthodoxy
Anthropology
Keywords: free market; neoclassical economics; radical liberalism

Le rendement et le butin. Regard écologique sur l'histoire du capitalisme, The Yield and the Booty. An Ecological Perspective on the History of Capitalism - Charbonnier, Pierre (Actuel Marx, 2013)
This article examines the history of globalized capitalism from the perspective of the relations to the environment which it helped to construct. It proposes a definition of globalized capitalism as a form of relation to nature. If philosophy has frequently postulated that modernity is characterized by the dissociation between the natural and the social, the history of the economic take-off of the states of Western Europe throws a singular light on this hypothesis. Combining a reading of Karl Polanyi and Kenneth Pomeranz, it can be argued that the logic of commodity always tends to render invisible the relations to the environment which define capitalism. The temporal and spatial lag between those populations which live the concrete experience of the industrial revolution and the enormous natural resources required for its appearance enable us to understand how it has been possible for the representation of the economy to become so radically dissociated from its natural metabolism.
History; Political Science
Keywords: globalized capitalism; nature and society; political thought

Cité et réciprocité, City and Reciprocity : The Role of Cultural Beliefs in the Roman Economy - Verboven, Koenraad (Annales. Histoire, Sciences Sociales, 2012)
La nouvelle économie institutionnelle est devenue populaire dans la recherche de l’économie antique depuis une dizaine d’années. Pourtant la notion de « croyances culturelles », qui joue un rôle central dans l’œuvre de Douglass North et dans les analyses du changement institutionnel par Avner Greif, a été largement ignorée. J’affirme qu’une approche néo-institutionnelle qui utilise cette notion de « croyances culturelles » offre une meilleure voie pour comprendre l’influence des idéologies et des valeurs morales sur l’économie antique que le modèle de Moses Finley. Des croyances culturelles ne sont pas des contraintes déterministes sur le comportement humain, mais elles aident à orienter les prises de décision et permettent d’anticiper les (ré) actions des autres. J’étudie deux ensembles de normes et de valeurs qui, dans la culture romaine, ont profondément marqué le cadre institutionnel de l’économie. L’un était centré sur la réciprocité. Ses normes et valeurs ont permis de construire et de maintenir des réseaux sociaux au-delà du groupe de la familia étendue avec ses affranchis. Elles étaient à la base du développement de la loi des obligations et de la représentation. L’autre se fondait sur la cité. Il a formé la culture politique en créant des droits et des obligations personnelles et en imposant des demandes légitimes aux élites politiques de défendre ceux-ci et de garantir et de stimuler des intérêts privés et communs. Le droit romain et la justice étaient ses résultats les plus importants. Idéologiquement, l’Empire romain se présentait comme une méta-cité qui incorporait les communautés locales qui, à leur tour, étaient graduellement transformées sur le modèle de la cité. Ces deux ensembles de croyances culturelles ont baissé les coûts de transactions, mais ils n’ont jamais menacé la prééminence de l’aristocratie locale et impériale. Vers la fin du IIe siècle de notre ère, les cités locales se sont affaiblies tandis que l’administration impériale se renforçait. Les aristocraties locales et régionales se sont tournées vers la bureaucratie et l’armée impériales pour maintenir leur rang social, leur influence et leur pouvoir. L’idéologie de la cité comme principe dominant de la culture politique devenait soumise à celle de l’empereur sacral, garant de la justice et de l’ordre divins. EN: New Institutional Economics have become popular in ancient economic history research the past decade. However, the notion of “cultural beliefs” that plays a central role in Douglass North’s recent work and in Avner Greif’s analysis of institutional change, has been largely ignored. I argue that a neo-institutional “cultural beliefs approach” offers a better way to understand the influence of ideology and moral values on the ancient economy than the Finley model does. Cultural beliefs are no deterministic constraints on human behavior but help to orient decision making and allow anticipating the (re)actions of others. I explore two key sets of norms and values in Roman culture that profoundly marked the economy’s institutional framework. One centered on reciprocity. Its norms and values supported social networks beyond the confines of the familia-freedmen group and underlay the development of contract and agency law. Another set rested on citizenship. It shaped political culture by creating individual rights and obligations and laying legitimate claims on political elites to enforce these and to take action to secure and stimulate private and common interests. Roman law and the distribution of justice was its prime off-spring. Ideologically the Roman Empire presented itself as a meta-city that incorporated local communities which in turn were gradually transformed to fit the civitas model. Both belief sets lowered transaction costs, but they never threatened the preeminent position of local and imperial aristocracies. Towards the end of the second century CE local communities became weaker while the imperial administration grew stronger. This caused local and regional aristocracies to turn to the imperial court and army for status, influence and power. The ideology of citizenship as the guiding principle of political culture gave way to that of the sacred emperor who guaranteed divine justice and order.
History
Keywords: Roman Empire; ancient economic history; ancient economies; cultural beliefs approach; institutional economics

La subsistance de l'homme. La place de l'économie dans l'histoire et la société - Praquin, Nicolas (Comptabilité Contrôle Audit, 2012)
Management Studies
Keywords: La subsistance de l'homme: La place de l'économie dans l'histoire et la société (Book); POLANYI; Karl; 1886-1964; The Livelihood of Man; book review; economic development; nonfiction

Les sociétés civiles entre risques ploutocratiques de la philanthropie et alternatives solidaires : une lecture polanyienne, The civil societies between the plutocratic risks of philanthropy and solidarity based alternatives : a Polanyian reading - Servet, Jean-Michel (Mondes en développement, 2012)
Tant dans les pays du Nord que dans ceux du Sud, un compromis entre une logique néo-libérale anti-étatiste et certains intérêts des organisations non gouvernementales a marqué la construction des sociétés civiles. Il s’est réalisé notamment à travers le social business soutenu par de grandes entreprises. En mobilisant le concept polanyien de principe d’intégration économique, l’analyse a pour ambition de comprendre les limites de ce nouveau modèle de philanthropie et ce qui le différencie de l’économie solidaire., Both in the Norths and in the Souths, a compromise between a neoliberal anti-statist logic and interests of non governmental organizations marked the construction of civil societies. This is achieved particularly through the social business supported by big companies. By mobilizing the polanyien concept of principle of economic integration, the analysis aims to understand the limits of this new model of philanthropy and what differentiates it of the solidarity based economy.
Development Studies
Keywords: NGOs; Polanyi; formal and informal sectors; institutional arrangements; nonprofit institutions; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; principes d'intégration économique; shadow economy; social business; économie solidaire

L'idéologie marchande au service de la biodiversité ? - Tordjman, Hélène; Boisvert, Valérie (Mouvements, 2012)
Economics
Keywords: biodiversity; markets

Retour sur le désencastrement - Brisset, Nicolas (Revue européenne des sciences sociales. European Journal of Social Sciences, 2012)
Our ambition is to point out that a fresh look at what is usualy considered to be Karl Polanyi’s magnum opus, The Great Transformation, opens some new prospects on its analytical. This interpretation qualifies some of the Hungarian author’s main critics, directed against his concept of desembeddedness. With this aim in mind, we re-interpret this debate in epistemological terms, i.e. the link between concepts and reality ; then we try to connect Karl Polanyi with the notion of performativity, which is today flourishing, above all within the field of economic sociology.
Economics
Keywords: Great Transformation; The (Book); Karl Polanyi; disembeddedness; great transformation; performativity; realism

Crise ? Vous avez dit : « Crise » ? - Naszályi, Philippe (Revue des Sciences de Gestion, 2012)
Crisis and institutional environment, crisis and organisational anticipations and crisis and consumer behaviour, just a few of the uses of the word « crisis » ; a word which, for over four years now, for the less perspicacious, and for over thirty years, for those who have been watching the bigger picture, has been the most appropriate word for this stage of development of the contemporary economic system. But exactly « what crisis are we talking about? ». That which is the result of a system, of an ideology which inhabits this system and of which the slightest of abilities was to try and present itself as unable to be exceeded, « by the end of the story ».' Yet, just as Max Weber stated, it seems that today's knowledge is still destined to be exceeded, particularly in the humanities, since society is constantly undergoing transformation. There is, therefore, no economic model which should not be discussed in order to be improved, or replaced. By delving into the ideal of Sismondi, today wrongfully forgotten, or in studying Karl Polanyi, we can gain much support for contemporary reflection which cannot continuously oppose Keynes, often summarised to the deficit of public policies and the « Chicago Boys » of which the action with Augusto Pinochet is truly symbolic of this « neo-liberalism» of American conservatives which is spreading across the globe, despite the crises which it has created. Crisis? Did you say: « Crisis' ? A question, and observation, but also in the manner of «great thinkers », solutions and alternatives which managers, in the widest sense of the term, « those who look after others and their businesses », provide through thirteen articles, collated into three thematic sections in this Spring edition which opens up new areas for reflection and action as « it is indeed time to put production before speculation, future investment before current satisfaction, sustainable employment before immediate profiteering ». (English)
Economics
Keywords: WEBER; Max; 1864-1920; consumer behavior; economic models; economic systems; humanities; institutional environment

Les réformes du marché du travail au Japon et en République de Corée: étude de cas comparée de l'élaboration des politiques dans les années 2000 - Yun, Ji-Whan (Revue internationale du Travail, 2011)
Dès la fin des années 1990, le Japon et la Corée ont entrepris des réformes du marché du travail souvent présentées comme un simple processus d'assouplissement. Partant, toutefois, de la perspective du «double mouvement» de Polanyi, l'auteur étudie la façon dont ces pays ont intensifié leur recours au marché tout en recherchant la stabilité sociale. Passant en revue les mesures législatives liées à la libéralisation de l'emploi et à la garantie de revenus, il analyse les différentes méthodes adoptées par ces deux pays pour réformer leur marché du travail. En conclusion, il avance que leurs voies de réformes divergentes tiennent à la spécificité des mécanismes utilisés pour élaborer leurs politiques ainsi qu'au contexte propre à chacun d'entre eux.
Political Science
Keywords: Corée R; Japan; Japon; commentaire; flexibilité du travail; politique du travail; protection sociale; segmentation du marché du travail; sécurité de l'emploi

Territoire, innovation et développement durable : l'émergence d'un nouveau régime conventionnel? - Buclet, Nicolas (Revue d'Économie Régionale & urbaine, 2011)
ENG TITLE: Territory, innovation and sustainable development: towards a new conventional regime? ABSTRACT: The paper examines the increasing number of diverse local development initiatives around the world aiming to break away from the predominant economic system. These initiatives, we argue, despite a somewhat visible disparity, largely rest on relatively similar principles, values and references. We argue that they are effectively laying the foundation for a new conventional regime more attuned to sustainable development goals. The paper analyses the characteristics of this regime, which refuses market dominance and favours reciprocal exchanges, as defined by Karl Polanyi. It is, nevertheless, necessary to question the potential and limitations of this conventional regime. (English)
Geography
Keywords: Territoire; conventions; development economics; développement durable; economic development; economics; environment; innovation; mathematical models; sustainable development; territory

Penser l’institution et le marché avec Karl Polanyi - Maucourant, Jérôme; Plociniczak, Sébastien (Revue de la régulation. Capitalisme, institutions, pouvoirs, 2011)
Bien que Karl Polanyi (1886-1964) n’ait jamais eu pour ambition « d’élaborer une théorie complète des institutions économiques », ce texte met en évidence qu’il y a, dans son œuvre, une analyse aussi implicite que profonde du marché appréhendé comme institution ou « processus institutionnalisé ». À l’encontre de la croyance économique conventionnelle, l’œuvre de Polanyi permet de comprendre que le marché, n’est ni spontané ni autorégulateur. Plus encore, à suivre Polanyi, le capitalisme ou « société de marché » se caractérise par un fait culturel spécifique : la croyance utopique en l’autorégulation marchande. Une origine de la crise économique actuelle peut ainsi être mise en évidence. Plus généralement, tout économiste contemporain soucieux des problématiques de l’institution et du marché peut, avec Polanyi, resituer de façon novatrice les marchés au sein des contextes socio-historiques dans lesquels ils se déploient. ENG translation: Although Karl Polanyi (1886-1964) never had the ambition "to elaborate a complete theory of economic institutions", this text emphasizes that there is in his work an analysis both implicit and profound Market as an institution or "institutionalized process". Contrary to conventional economic belief, Polanyi's work makes it possible to understand that the market is neither spontaneous nor self-regulating. Moreover, to follow Polanyi, capitalism or "market society" is characterized by a specific cultural fact: the utopian belief in mercantile self-regulation. An origin of the current economic crisis can thus be highlighted. More generally, any contemporary economist concerned with the problems of the institution and the market can, with Polanyi, innovatively place markets in the socio-historical contexts in which they unfold.
Economics
Keywords: capitalisme; crise; encastrement; institution; marché autorégulateur; marchés; société de marché; utopie

Les sciences sociales africanistes à l’épreuve des projets de développement. Peuvent-elles dépasser l’opposition entre l’universalisme de l’économie et le relativisme de l’anthropologie ? - Hugon, Philippe (Cahiers d’études africaines, 2011)
RésuméLes disciplines économiques et anthropologiques, notamment africanistes, ont été généralement caractérisées par des exclusions et des cloisonnements. L’économie s’intéresse principalement aux sociétés marchandes et capitalistes occidentales et mobilise des catégories à vocation universelle alors que l’ethnologie ou l’anthropologie prennent pour champ les sociétés « primitives » exotiques ou premières, et privilégient les catégories et représentations des acteurs. Le champ du développement a été un lieu de rencontre obligé des deux disciplines. L’économie a cherché à aborder les sociétés non occidentales et l’anthropologie a été confrontée aux projets de développement. Cet article rappelle les oppositions historiques entre les éclairages économiques et anthropologiques avant de présenter certains enjeux méthodologiques et épistémologiques d’une anthropologie économique du développement en l’illustrant par la filière coton., Abstract ENG: Economics and anthropology as africanist social sciences have known a separate evolution. Economics are mainly interested by capitalism and Western societies and mobilize universalist concepts. Ethnology or anthropology on the other hand study more traditional, “primitive” or exotic societies. Howewer the two meet and have some confrontation when they study development. Firstly, this article recalls the historical oppositions between the economical and the anthropological points of view. Secondly, it presents some of the methodological and epistemological stakes of development economic anthropology. Lastly this paper illustrates this debate in examining the case of the chain value within the economic overall process of coton production and exchange.
Economics; African Studies
Keywords: africanist social science; cotton production; exchange

Le concept de « marchandise fictive », pierre angulaire de l'institutionnalisme de Karl Polanyi ? - Postel, Nicolas; Sobel, Richard (Revue de philosophie économique, 2011)
The notion of “fictitious commodities” is not simply a convenient heterodox slogan to criticize the radical limits of any trade system and the analytical limits of the dominant theory. It is rather the foundation of the institutional perspectives that underlie all Karl Polanyi’s sociohistoric analyses. This article explains and articulates both the theoretical level using the institutional approach to commodities and a philosophical level using a broad definition of the economy. There is, however, a limit to the notion of the institution, which connects both levels: it is not articulated practically such that the potential and critique of this construct may be weakened.
Sociology; Economics
Keywords: capitalisme; institution; marchandises fictives; raison pratique; économie substantive

Y a-t-il une économie sartrienne ? - Kail, Michel; Sobel, Richard (L'Homme & la société, 2011)
RésuméEn dépit de l’absence d’un exposé économique systématique dans l’œuvre de Sartre, nous soutenons qu’il y a bien une économie sartrienne, même si celle-ci est encore à développer. Le statut que Sartre réserve à la « rareté » lui permet de faire un pas supplémentaire vers la critique de l’économisme par rapport à celui déjà effectué par Karl Polanyi, qui s’est contenté de récuser la confusion entretenue entre l’économique et sa définition formelle. La rareté, nous enseigne Sartre, ne saurait en effet être soumise au traitement de la raison instrumentale, mais considérée, ajoute-t-il, comme un fait humain dans l’histoire. Aussi, l’analyse économique ne doit-elle pas s’appuyer sur la notion de « nature » et la thématique de l’homme confronté à la nature, en l’occurrence « ingrate », mais articulée sur la notion de « monde » telle que la philosophie sartrienne l’élabore., Despite the absence of a systematic analysis of economics in Sartre’s work, we argue that there can indeed be said to be a Sartrean economics, even if it is one that still awaits development. The status which Sartre accords to the concept of Scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason, but considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man’s confrontation with a typically ungrateful Nature, but articulated through the concept of World as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: SARTRE; Jean-Paul; 1905-1980; economic systems

À propos de « ceux qui sont en dehors de la société ». L'indigent et l'assistance publique au Québec dans la première moitié du XXe siècle - Petitclerc, Martin (Revue d'histoire de L'Amerique francaise. automne2011/hiver2012, Vol. 65 Issue 2/3, p227-256. 30p., 2011)
The “ Loi établissant le service de l'assistance publique" (Public Welfare Act) sparked considerable controversy after its adoption in 1921 .The Act provided for provincial and municipal grants to private and religious institutions providing shelter to the poor and destitute. Led by Henri Bourassa, among others, the debate concerned the problem of state intervention in an area traditionally conceived of as the responsibility of the Church. In contradiction to Bourassa's theories, most historians analyzed the A c t through the rubric o f modernization as a necessary affirmation of State prerogatives in the area of social protection. In this article, we argue that this Act is an attempt (largely successful) to consolidate a form of liberal governmentality based on, since the 19th century, what Karl Polanyi termed “the figure of the pauper" According to this perspective, the 1921 A c t is not a significant stage in the age-old struggle between Church and State, but rather a time of reform in liberal politics in regards to "the indigent 'The latter leggally defined as unable to work and without family support, and therefore “ outside of society," an expression of the day, allowed justifying the development o f a private/public system of charitable assistance against the project o f social policies founded on a universal conception of social rights. The article presents this dynamic through an analysis of the contentious issue of the rights of indigents to public assistance. (English)
History
Keywords: BOURASSA; Henri; 1868-1952; Canada; Quebec; church & state - Canada; liberalism - Canada; poor people - Canada; poor people - government policy; poor people - services for - history; public welfare - Canada - history

Polanyi contre Freeman. (Polanyi against Freeman. With English summary.) - Postel, Nicolas; Sobel, Richard (Revue de la Regulation, 2011)
The dominant approach of CSR is based on the concept of "stakeholders" (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi's institutionalism.
Sociology; Economics
Keywords: Marxian; Sraffian; business objectives of the firm; corporate culture; current heterodox approaches: institutional; current heterodox approaches: socialist; diversity; evolutionary; social responsibility

L’Encastrement Social des Marchés. Éléments théoriques et empiriques pour une analyse en termes de réseaux relationnels - Plociniczak, Sébastien (Revue de la régulation. Capitalisme, institutions, pouvoirs, 2010)
Despite the core role played by market in economic theoretical frameworks, the market is still little addressed and finally remains a vague type at best equivoque. This thesis aims to contribute to a collective pattern devoted to the diversification of market analysis since the 70s. This collective pattern is the New Economic Sociology, founded and built on a central idea, i.e. the embeddedness. In the perspective of Karl Polanyi and Mark Granovetter’s works, the thesis intends thus to enlighten first the use of this idea as the necessary clarification does not occur until now. Then, it puts forward the fact that an analysis of markets may definitely benefit from a deeper understanding of the multilateral logic of relational networks. At last, on the base of main assumptions defined in this thesis, the robustness of the heuristic contractual model of the Transaction Costs Economics depicted by Oliver E. Williamson is assessed.
Economics
Keywords: capital social; contrat; coûts de transaction; embeddedness; encastrement; forme hybride; institutions; marchés; réseaux relationnels; social capital

Hannah Arendt et Karl Polanyi : le libéralisme économique, l'effondrement du politique et la société de masse, Abstract - Azam, Geneviève (Revue du MAUSS, 2010)
RésuméDans les années 1930, Hannah Arendt et Karl Polanyi ont partagé l’expérience du déracinement, de la désolation et celle de l’effondrement de la civilisation du xixe siècle. À partir de l’analyse de la société de marché pour K. Polanyi et de la condition de l’homme moderne pour H. Arendt, ils montrent comment l’économisme et la construction d’une société économique au xixe siècle, sont à l’origine de l’avènement de la société de masse qui porte des tendances totalitaires. Leur regard croisé donne des clés de compréhension des menaces qui pèsent qui pèsent sur nos « sombres temps »., In the 1930s, H. Arendt and K. Polanyi shared the experience of rootlessness and the collapse of nineteenth century civilisation. Through the analysis of the market society (K. Polanyi) and the condition of modern man (H. Arendt), they analyse how economicism and the advent of an economic society in the nineteenth century have engendered mass societies which carry totalitarian tendencies. This double perspective gives some keys to understand the threats of our « dark times ».
Economics
Keywords: ARENDT; Hannah; economic liberalism; mass society

Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire - Servet, Jean-Michel (Revue Tiers Monde, 2010)
English translation: Karl POLANYI has an indirect understanding of the societies that were part of the Third World in the fifties. From anthropologists he came out with the principle of reciprocity. He then opposed this principle of economic integration to both redistribution and market principles. Reciprocity can neither be viewed as a practice of primitive societies (as in evolutionist approaches) nor as a gift and counter-gift exchange. Reciprocity needs to be understood as a social whole and through a claimed mutual dependency. In this approach, reciprocity allows to set up the definition of the solidarity-based economy. Jean-Michel Servet, “ Le principe de réciprocité chez Karl Polanyi, contribution à une définition de l'économie solidaire ”, Revue Tiers Monde 2/2007 (n° 190) , p. 255-273
Development Studies
Keywords: reciprocity

Au-dela de la dichotomie marche-institutions: L'institutionnalisme de Douglass North face au defi de Karl Polanyi. (With English summary.) - Didry, Claude; Vincensini, Caroline (Revue Francaise de Socio-economie, 2010)
On the basis of the "challenge" North (1977) identified in the works of Polanyi, we propose to outline the originality of North's institutionalism, especially in comparison with "new institutionalism" in economics as well as in sociology. Far from endorsing the dichotomy between market and non market dimensions of economic activities at the basis of the analyses of Williamson and Granovetter, North's definition of institutions as "rules of the game" allows him to conceive of institutions as the institutional foundations of the market and therefore as explanatory principles of historical dynamics.
Sociology
Keywords: Austrian; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought since 1925; institutional

L’« institution » selon Karl Polanyi. Fondements et mise en perspective contemporaine - Maucourant, Jérôme; Plociniczak, Sébastien (Tracés. Revue de Sciences humaines, 2009)
Depuis les années soixante-dix, certains économistes ont tenté de répondre aux difficultés de plus en plus nombreuses qu’ils rencontraient en réélaborant le concept d’institution. Cette tentative « néo-institutionnaliste » fut porteuse de malentendus. L’autonomisation progressive de l’économie comme savoir s’était, en effet, construite sur l’occultation délibérée de toutes sortes de fondements extra-économiques. La quête de tels fondements, dans l’intention d’asseoir scientifiquement la conna...
Economics
Keywords: MALTHUS; T. R.; RICARDO; David; institutionalist approach

Karl Polanyi : une voix du siècle passé, Abstract - Cangiani, Michele (Revue du MAUSS, 2009)
RésuméSituer Karl Polanyi dans son temps et par rapport aux grandes théories sociales du passé, y compris celle de Marx, nous permet de mieux comprendre les problèmes du temps présent. C’est de ce point de vue que l’article cherche à mettre brièvement en relief quelques aspects de la contribution de Polanyi à la connaissance historique, à la critique de la science économique et à la théorie politique., To consider Karl Polanyi’s thought in relation to his time and to great social theories of the past, Marx’s theory to begin with, can improve our understanding of problems of current times. This is the starting point of this article’s attempt to synthetically focus some aspects of Polanyi’s contribution to historical knowledge and political theory, and of his critique of economics.
History
Keywords: political theory

Karl Polanyi et La Pédagogie De L'incohérence - Gazier, Bernard; Mendell, Margie (Annals of Public and Cooperative Economics, 2009)
Cet article vise à examiner de manière critique et constructive l'actualité de la pensée de Karl Polanyi pour comprendre le développement de l'économie plurielle au XXIe siècle et pour agir sur celui-ci. Il montre la très grande actualité de cette pensée, ainsi que la nécessité de s'intéresser à l'œuvre entière de Karl Polanyi, et pas seulement à«La grande transformation». Partant des usages multiples du concept d'encastrement et de désencastrement, il relie les propositions inspirées par Karl Polanyi sur «le processus institué de démocratisation économique»à des développements récents tant pratiques que théoriques: les «>marchés transitionnels du travail» et la «nouvelle finance publique». ENG: The aim of this article is to examine critically and constructively the current state of Karl Polanyi's thinking in order to understand and act on the development of the pluralist economy in the twenty-first century. It shows the very topicality of this thought, as well as the need to take an interest in the entire work of Karl Polanyi, not just "The great transformation". Starting from the multiple uses of the concept of embedding and disencing, he links the proposals inspired by Karl Polanyi on "the instituted process of economic democratization" to recent practical and theoretical developments: "transitional labor markets" and " New public finance ".
Economics
Keywords: economic democratization; instituted economic process; new public finance; pluralist economy; transitional labor markets; transitional labour markets

Encastrement et nouvelle sociologie économique : de Granovetter à Polanyi et Mauss - Laville, Jean-Louis (Revue Interventions économiques. Papers in Political Economy, 2008)
Le concept d’encastrement s’est imposé dans la nouvelle sociologie économique. Ce texte souligne sa polysémie. Dans une première partie, il rappelle les deux acceptions politique et réticulaire respectivement adoptées par Granovetter et Polanyi. Rapportée à la modernité démocratique, la démarche de Polanyi permet de mettre en évidence un double mouvement caractérisant les rapports entre économie et société, dont les grands traits sont synthétisés dans la deuxième partie. Si l’on adopte une telle lecture, la convergence entre Polanyi et Mauss apparaît alors dans une approche plurielle de l’économie, présentée dans la troisième partie. Selon l’hypothèse esquissée dans la quatrième partie, une telle lecture suggère d’approfondir la teneur des changements institutionnels susceptibles de conforter la pluralité de l’économie, autrement dit de participer à son « ré-encastrement » démocratique. The concept of embeddedness has imposed itself in the New Economic Sociology. This paper highlights the multiple meanings of this term. In a first part, we discuss the political and reticular meanings adopted by Granovetter and Polanyi respectively. In the context of modern democracy, the work of Polanyi shows a double movement characterizing the relations between economy and society, which we develop in the second part. With such a perspective, the convergence between Polanyi and Mauss is highlighted in a plurial approach of the economy, which we discuss in the third part. The hypothesis presented in the fourth part leads us to analyze the content of institutional changes which can confirm the plurality of the economy, and to participate in its democratic « reembeddedness ».
Sociology; Economics
Keywords: GRANOVETTER; Mark; MAUSS; Marcel; 1872-1950; economic sociology; encastrement; niveau d’intégration; sociologie économique

La dépolitisation de la notion de « capital social » : pourquoi pas un retour à Karl Polanyi? - Bibeau, Gilles (Anthropologica, 2008)
Anthropology
Keywords: social capital

Le capital et la question nationale - Maucourant, Jérôme; Tinel, Bruno (Actuel Marx, 2008)
Nations are the forms of political organization which peoples construct for themselves. It is a commonplace to state that globalization tends (for the better) towards the end of nations. However the history of capitalism shows that such a hypothesis is questionable. Globalization is merely a stage in the development of capitalism, which has always leaned on certain nations to secure its deployment: England in the past, the U.S. today. The real question is thus that of the hegemony of one nation over other nations and, ultimately, the question of democracy, the sovereignty of peoples in the face of capital.
Economics
Keywords: democracy; globalization

Une révolution bureaucratique britannique ? - Gales, Patrick LE; Scott, Alan (Una revolución burocrática británica ? Autonomía sin control o « freer markets, more rules »., 2008)
This article originated with a puzzle : how best to account for changes in the behavior of groups, organizations and individuals in Great Britain ? A detailed analysts of what Weber and Polanyi identified as interdependencies between state and market, and of the state's role in creating the market, led to the decision to adapt the notion of bureaucratic revolution put forward by Weber. We argue that the British bureaucratic revolution is reflected in the fact that the state plays an essential role in social change by creating rules and institutions that lastingly orient actors' behavior. The examples of health and local authorities are then used to identify mechanisms that were influential throughout a ten-year period specifically the introduction of competition features (rewards and punishments) and of auditing and inspection. If our interpretation is accurate, the effects of this bureaucratic revolution may well come to be felt in contexts other than Great Britain. (English)
Sociology; Political Science
Keywords: 1997-2010; Great Britain - social conditions - 1945-; WEBER; Max; 1864-1920; bureaucratization; economic policy; social goals; socioeconomics

L'innovation sociale dans les services d'aide a domicile. Les apports d'une lecture polanyienne et feministe. (With English summary.) - Degavre, Florence; Nyssens, Marthe (Revue Francaise de Socio-economie, 2008)
The aim of this contribution is to analyze the dynamic of social innovation of home-care services. Based on the works of Polanyi which analyse socio-economic dynamics and on feminist theories in the field of care, we develop an original grid of analysis developing criteria to grasp the processes of social innovation and to highlight the peculiarities of gender relationships at stake in these services. We also suggest normative criteria to evaluate the quality of social innovation. We apply this conceptual framework to the empirical field of new home-care services, which have emerged 20 years ago, and provided to elderly dependents in Wallonia.
Interdisciplanary
Keywords: economics of the elderly; economics of the handicapped; feminist economics; health; non-labor market discrimination; non-labour market discrimination; personal; professional; and business services; social innovation

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Sociology; Economics
Keywords: criticism of economism; formal economy; general economics

La connaissance, une marchandise fictive, Knowledge, a Fictitious Commodity - Azam, Geneviève (Revue du MAUSS, 2007)
Cet article se propose d’analyser le sens de l’invention d’une « économie de la connaissance » et de la transformation de la connaissance en bien économique, illustrée par la transformation des droits de propriété intellectuelle. En poursuivant l’analyse de Karl Polanyi à propos des « quasi-marchandises », la connaissance doit plutôt être considérée comme une marchandise « fictive ». C’est le point de vue adopté dans cet article qui montre comment la tentative actuelle de rendre cette fiction effective menace la connaissance elle-même en l’assignant à un rôle instrumental., This article offers some reflections on the sense given to the invention of a « knowledge economy » and on the conditions of knowledge commodification, as illustrated by the current changes in knowledge property rights. Elaborating on Karl Polyani’s argument about « quasi-commodities », we have to regard knowledge as a « fictitious commodity » rather than a simple commodity. It is the point of view we have adopted in this article, which shows that the current attempts at giving this fiction more actuality pose a threat to knowledge itself by confining it to an instrumental function.
Economics
Keywords: fictitious commodities; knowledge

Devons-nous mériter notre salaire ?, Do We Have To Deserve Our Salary ? - Girardot, Dominique (Revue du MAUSS, 2007)
L’idée qu’une rémunération juste du travail relève d’un calcul du mérite tend à s’imposer comme un lieu commun. Les présupposés et les conséquences d’une telle représentation sont ici interrogés dans la perspective ouverte par les analyses de Polanyi sur les effets dévastateurs de la fiction d’un marché autorégulateur lorsqu’elle atteint des réalités comme celles – parmi d’autres – du travail. Le paradigme du don et le concept arendtien de l’action permettent d’identifier, dans le besoin de reconnaissance, à la fois la source de l’efficacité de la fiction d’un mérite rétribuable et les raisons de son inévitable échec pratique. Non qu’on ne puisse instituer une rémunération au mérite ; mais c’est au prix d’une réification de l’activité humaine, lourde de menaces pour la réalité que nous partageons. ENG: The idea that a righteous work’s remuneration is to be measured by merit is tending to stand out as a commonplace. Presuppositions and consequences of such an idea are questioned here from Polanyi’s viewpoint on devastating effects of the selfregulating market’s fiction when realities as work are reached. The gift’s paradigm and Hannah Arendt’s concept of action allow to point out that the need of acknowledgement both gives its efficiency to the fiction of a payable merit and causes its inevitable practical failure. Not that it’s impossible to institute merit’s remuneration ; but it’s at the cost of reifying human activity, that threatens the reality we share.
Philosophy
Keywords: ARENDT; Hannah; payable merit; self-regulating market

Licenciements collectifs : le prix d'une dette symbolique, Massive Layoffs : The Price of a Symbolic Debt - Malsan, Sylvie (Revue du MAUSS, 2007)
Les licenciements massifs que connaît depuis vingt ans l’industrie française conduisent les ouvrier(ière)s à exprimer des demandes de réparation symbolique sous des formes nouvelles, dont l’interprétation échappe au paradigme classique de la lutte des classes. C’est avec Karl Polanyi, pour qui l’activité économique n’est pas autre chose que la vie elle-même, et Marcel Mauss, qui a posé le don au centre des relations sociales, que nous tentons de réinterroger la relation de travail dans son inégalité constitutive, mais aussi dans ce qu’elle représente pour l’ouvrier(ière) comme don de soi. En nous appuyant sur les données empiriques d’une enquête menée dans la région de Cherbourg, nous entendons caractériser le lien symbolique existant au coeur même du contrat de travail., ENG: Massive layoffs have occurred during the last twenty years in French industry which brings workers to express demands for symbolic reparation under new forms. This phenomena cannot be interpreted by classic paradigms as class struggles. Here we try to analyse working relationships through Polanyi and Mauss approaches. The first one considers that economic activity is nothing else that life itself ; the second puts gift at the core of social relationships. Following these authors, we characterize the symbolic link between employer and employee, which is anchored into employment contract. Our empirical data are based on research carried on in Cherbourg’s area (France).
Anthropology
Keywords: France; labour; symbolic debt

Le problème du désencastrement, The Problem of Disembeddedness - Velly, Ronan Le (Revue du MAUSS, 2007)
Cet article revient sur la réception du travail de Karl Polanyi par plusieurs chercheurs importants de la nouvelle sociologie économique. Il montre que Polanyi a fait l’objet de deux types de critiques ayant en commun de contester la possibilité du désencastrement. Ces critiques sont discutables, et il est possible de donner une explication des malentendus liés à cette question en distinguant deux notions complémentaires d’encastrement, la première insistant sur les conditions sociales à partir desquelles les échanges marchands sont nécessairement construits et la seconde décrivant les degrés variables de différenciation des économies., EN: This paper discusses the reception of Karl Polanyi’s work by some leading scholars of the New Economic Sociology. It shows that Polanyi has received two different kinds of criticisms that, both of which, contest that there can be such thing as disembeddedness. These criticisms are not very justified and it is possible to give an explanation of this misunderstanding by distinguishing between two different and complementary notions of embeddedness, a first one that puts the stress on the social conditions upon which economic transactions are necessary carried out and a second one that describes how much economies are differentiated.
Sociology
Keywords: critique; disembeddedness

Le « Gas Argentine » Revisite: De L'utopie Libérale Au Retour De La Politique… - Blaum, Luis (El «caso argentina» revisitado. De la utopía liberal al regreso de la potítica…., 2007)
Argentina constitutes a revealing textbook case of the link between the liberal utopia of an auto-regulated market, commodity fetishism and economists' theories. How does economic liberalisation, backed by a law on currency convertibility, resolve the crisis of political representation affecting the country since the emergence of Peronism, the «voice of the voiceless», in the 1940s? The liberal utopia of markets' auto-regulation associates taking root in social life with having money, by means of what Marx called the «vulgar economy». From this viewpoint, the monetary crisis of 2001, a real social tragedy, illustrates Polanyi's thesis: liberal utopia's stumbling blocks force societies to give markets roots which have political and social dimensions. But, conveyed by economic thought, commodity fetishism continues to play an active role in exiting a crisis. The political position is perilous and based on a scientific approach that makes people believe that social reality can be completely manipulated. (English)
Economics
Keywords: Argentina; MARX; Karl; 1818-1883; commodity fetishism; financial crises; financial crisis; utopia

Une fondation Polanyi : un projet toujours actuel, A Polanyi Foundation : Still Up To Date - Caillé, Alain (Revue du MAUSS, 2007)
La pensée de Polanyi peut être vue comme une sorte de lieu géométrique entre des courants de pensée de gauche très divers, de la gauche de gauche au centre gauche. Cet article montre comment, entre 1995 et 1999, le nom de Polanyi a en effet servi de point de ralliement à des dizaines d’intellectuels (sociologues, économistes, philosophes...) connus en France et en Europe, ce qui n’a pas été sans impact politique. Une perspective toujours d’actualité ?, Polanyi’s throught can be seen as some sort of smallest denominator common to diverse spheres of the Left ranging from ultra to central Left. The article shows how between 1995 and 1999 Polany’s name has permitted to gather dozens of well-known intellectuals (sociologists, economists, philosophers) in France and in Europe and how this gathering has had some political impact. A still urgent perspective ?
Sociology
Keywords: plural economy; radical social democracy; social-démocratie radicale; économie plurielle

Actualité de Karl Polanyi, The Actuality of Karl Polanyi - Caillé, Alain; Laville, Jean-Louis (Revue du MAUSS, 2007)
Que peut-on retenir de l’œuvre de K. Polanyi en comparaison, notamment, de celles de Marx ou de Weber ? Cet article fait le point à la fois sur les contributions historiques et anthropologiques de Polanyi à l’histoire du marché et sur son aspiration à un socialisme associationniste, et il conclut que, audelà des nécessaires rectifications et actualisations, K. Polanyi reste la source d’inspiration principale pour un socialisme radical à visage humaniste., What must be kept of K. Polanyi’s legacy as compared, especially, to those of Marx or Weber ? This article provides an evaluation both of the anthropological and historical contributions of Polanyi to the history of market(s) and of the present meaning of his advocacy of an associationist socialism. It concludes that, once the necessary corrections and rectifications are made, Polany remains our main resource to think a radical and democratic socialism with a humanist face.
Sociology
Keywords: capitalism; capitalisme; democracy; démocratie; marché; markets; socialisme associationniste; solidarity economy; économie solidaire

Mort et résurrection du capitalisme libéral, Death and Resurrection of Liberal Capitalism - Laval, Christian (Revue du MAUSS, 2007)
Pour comprendre La Grande Transformation de Karl Polanyi, il faut la replacer dans le contexte des années 1930 et 1940, époque de contestation générale du vieux libéralisme « manchestérien ». L’article compare les positions de quatre auteurs contemporains : Karl Polanyi, Joseph Schumpeter, Friedrich von Hayek et Walter Eucken. Cette comparaison montre d’abord que Polanyi n’était pas le seul à constater la fin du cycle libéral du capitalisme. Elle montre ensuite que la question portait aussi sur le type d’intervention de l’État. La nouveauté introduite par le néolibéralisme réside dans le fait que le marché n’est pas une nature, mais un ordre politiquement construit., ENG: To have an accurate reading of Karl Polanyi’s The Great Transformation, the reader should put his work back in its context of the 1930’s and 1940’s, in a time of widespread criticism of the old « manchesterian » liberalism. The text draws a parallel between the points of view of four contemporary writers : Karl Polanyi, Joseph Schumpeter, Friedrich Von Hayek et Walter Eucken. First and foremost, it shows that Polanyi was not the only writer to note the end of the liberal cycle of capitalism. Then, it emphasizes the fact that the debate was focused on the type of state intervention. The originality brought about by neoliberalism lies in the conception of market, which is no more considered as natural but as a political construction.
Sociology
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; SCHUMPETER; Joseph Alois; 1883-1950; liberal capitalism; neoliberalism

Karl Polanyi, une biographie intellectuelle - Maucourant, Jérôme (Revue du MAUSS, 2007)
I will endeavor here to retrace the major stages of life and career of Karl Polanyi and the genesis of his main ideas in the first part of the TWENTIETH century marked both by the occurrence of major disasters and the Effacement of the first market society that had taken shape in the nineteenth century.
Sociology; Political Science
Keywords: biography; capitalisme; démocratie; marché; socialisme

Le marché, une institution entre économie et histoire - Maucourant, Jérôme (Cahiers lillois d'économie et de sociologie, 2007)
"L'hypothèse de l'article est la suivante : il n'est pas possible de parler rigoureusement d'un concept de « marché » en science économique, car ce concept est en réalité une notion floue, au mieux ambivalente. En revanche, le recours à d'autres sciences sociales, comme l'histoire et la sociologie, peuvent aider à la construction d'un concept de marché. Ainsi, le travail de Karl Polanyi et les travaux d'historiens contemporains, notamment ceux d'Alain Guéry, semblent utiles pour mieux distinguer le marché propre à la « société de marché » au sens de Polanyi des marchés caractéristiques des économies archaïques ou d'Ancien régime. L'histoire des idées et la réhabilitation du travail de Montchrestien, contre le jugement hâtif de Schumpeter, est mobilisée pour illustrer l'hypothèse de l'article. Il est enfin suggéré que ni l'approche en terme d'équilibre général, ni les travaux d'Israël Kirzner n'ont eu de valeur heuristique en ce qui concerne la présente problématique." ENG translation: "The topic of the paper consists in arguing that it is not yet possible to have a rigourous concept of « market », as so far as economics is concerned. Nor equilibrilim theory nor kirznerian approach have a real interest for the precise task of conceptualising market as such. At best, « market » is a undetermined notion or, in some case, has even a double meaning (market place and selfregulating market). Nevertheless, thanks to other social science, i.e. history and sociology, il is possible to elaborate a concept of market. Works of Karl Polanyi, but also more recent contributions of a historian of french Ancien Régime economy, Alain Guéry, are usefull from this point of view. Then, a clear distinction seems to be done between market of modern « market society ». The paper insists also in giving ti the Montchrestien Traicté de l'Œconomie politique a importance denied by Schumpeter. "
Economics; Sociology
Keywords: economic theory; markets

Karl Polanyi et le processus institué de démocratisation politique, Karl Polanyi and the Instituted Process of Political Democratization - Mendell, Marguerite (Revue du MAUSS, 2007)
Cet article porte sur le « processus économique institué » de Karl Polanyi. Il s’appuie sur certains de ses écrits moins connus, qui précèdent et suivent la publication en anglais de la Grande Transformation, dans lesquels Polanyi insistait en particulier sur la capacité des individus et des collectivités à agir sur leur propre destinée. Ces écrits nous aident à conceptualiser les processus de transformation institutionnelle qui caractérisent la société contemporaine. Cet article s’intéresse à l’impact de la société dite civile sur l’innovation en matière de politiques ou d’institutions, sur les préconditions qui institutionnalisent, pour ainsi dire, ces pratiques – qui se transmettent ensuite horizontalement aux sous-systèmes institutionnels et verticalement aux institutions macro ou gouvernantes. ENG: This article bears on Polanyi’s « instituted economic process » and uses a range of not very well known articles published before and after The Great Transformation where Polanyi insisted on the capacity of individuals and communities to shape their own destiny. Here we are particularly interested in the impact of civil society on political innovation which percolates both along horizontal or vertical lines.
Economics; Sociology
Keywords: instituted economic process

Au-delà d'une certaine lecture standard DE La Grande Transformation - Plociniczak, Sébastien (Revue du MAUSS, 2007)
Whereas a largely conveyed standard reading of The Great Transformation lets one think that Karl Polanyi establishes the effective birth certificate of a self-regulated market at the nineteenth century in the West, this text suggests that The Great Transformation makes Polanyi the author of a criticism of the theoretical fiction of the self-regulated market, and the historian of this acting fiction which directs individual behaviors and transforms in-depth the Western societies of the nineteenth century.
Economics
Keywords: Great Transformation; The (Book); great transformation; reinterpretation

Karl Polanyi, Viviana Zelizer et la relation marchés-société - Steiner, Philippe (Revue du MAUSS, 2007)
After a brief study on the place given to Polanyi’s thought in contemporary economic sociology, the paper examines Zelizer’s works on money and her opposition to Polanyi’s thesis on embeddedness, grounded on the symetry between markets and social life.
Sociology
Keywords: ZELIZER; Viviana; embeddedness

L'utopie de l'économie de la connaissance - Azam, Geneviève (Problèmes économiques n. 2901, 2006)
"L'expression "économie de la connaissance" a, en ce début du XXIe siècle définitivement remplacé celle, très en vogue à la fin des années 1990, de "nouvelle économie". Les sociétés les plus avancées auraient désormais atteint un nouveau stade du développement économique dont la connaissance serait le facteur essentiel. Cette idée laisse supposer que jusque-là, celle-ci ne jouait qu'un rôle secondaire dans le processus productif. L'auteur se propose d'expliquer le sens et les implications que ce nouveau statut confère au savoir et à la recherche. Pour mieux comprendre ce qui est à l'oeuvre avec l'invention d'une "économie de la connaissance", elle analyse tout d'abord, à travers l'évolution récente des droits de propriété intellectuelle, les conditions de la transformation de la connaissance en bien économique. S'appuyant sur les travaux de Karl Polanyi, à propos des "quasi-marchandises", l'auteur montre ensuite qu'en réalité celle-ci est une marchandise "fictive" et que la tentative actuelle de lui assigner un rôle instrumental constitue pour elle-même une grave menace." ENG: Building on the work of theKarl Polanyi , on the subject of "quasi-merchandise", the author then shows that, in reality, the latter is a "fictitious" commodity and that the current attempt to assign to it an instrumental role constitutes for itself a serious threat
Economics
Keywords: Lisbon Strategy; biodiversity; economic property; economy of knowledge; ethics; evaluation; intangible assets; intellectual property; patents

Karl Polanyi et la séparation institutionnelle entre politique et économie - Buğra, Ayşe (Raisons politiques, 2005)
This article explores Karl Polanyi’s analysis of the institutional separation of politic and the economy in the context of the 19th century market economy. The contribution his analysis could make to the quest for viable alternatives to the contemporary neo-liberal international order depends on how we construe two key concepts in his work, “disembeddedness” and “countermovement”. In this regard the author suggests that: 1) In Polanyi’s work the disembedded economy appears not as a sociological reality but as a political project, and 2) Polanyi’s analysis of the countermovement does not justify all types of resistance to the market economy as humane and politically acceptable.
Economics; History
Keywords: institutional separation

Le port de commerce : un concept en débat - Graslin, Laetitia; Maucourant, Jérôme (Topoi, 2005)
Economics; History
Keywords: Dahomey and the Slave Trade; port of commerce

Le troc et la monnaie dans la pensée de Polanyi - Maucourant, Jérôme (2005)
Relire K. Polanyi nous affranchit d'une double illusion. Selon la première, l'homme est essentiellement un atome utilitaire exploitant les gains supposés de l'échange, cette vieille « fable du troc » n'étant pas remise en cause par l'économie des « coûts de transaction ». La seconde illusion, construction hétérodoxe voulant s'affranchir de cette fable, attribue à la monnaie les traits d'une institution aussi transhistorique qu'universelle. Certes, de nombreux phénomènes qualifiés de « troc » sont en réalité issus de la destruction d'ordres monétaires. D'ailleurs, K. Polanyi, commentant Aristote, montrait déjà que le dogme de la naturalité du troc est une projection des a priori de la société de marché. Mais, ceci ne signifie pas que la monnaie soit « souveraine » : seules les communautés politiques sont souveraines, seule la réciprocité, au sens de l'école maussienne, est un universel, le troc pouvant être « enchâssé » dans l'économie. Review Polanyi frees us a double illusion. According to the first, man is essentially a utilitarian atom exploiting the supposed gains of exchange, this old "barter fable" not being called into question by the economy of "transaction costs". The second illusion, a heterodox construction wishing to free itself from this fable, attributes to money the features of an institution as transhistorical as a universal one. Certainly, many phenomena called "barter" are in fact derived from the destruction of monetary orders. Besides, K. Polanyi, commenting Aristotle, already showed that the dogma of the naturalness of barter is a projection of a priori of the market society. But this does not mean that money is "sovereign": only political communities are sovereign, only reciprocity, in the sense of the Maussian school, is a universal, barter can be "enshrined" in the economy.
Economics; Political Science
Keywords: barter; universal barter

L'ère de l'opulence selon Polanyi - Maucourant, Jérome; Vivel, Christel (Economies et sociétés, 2005)
L'article expose la problématique d'un texte peu connu de Polanyi datant de 1959. Prétextant un commentaire de L'ère de l'opulence de Galbraith, il soutient que le naturalisme de l'économie dominante nous interdit de comprendre la signification véritable de la rareté. Polanyi montre alors que les oppositions classiques entre liberté et égalité, économie et démocratie, peuvent être dépassées dans le cadre d'une société nouvelle abolissant la séparation institutionnelle de l'économique et du politique. Ces thèses de Polanyi sont imprégnées d'un aristotélisme tenant compte des déchirures sociales que furent le machinisme et les fascismes. KM: One aims at presenting a unknown Polanyi's text. Starting with a comment of the Affluent Society from Galbraith, we explain that the mainstream economics'naturalism prevents us from understanding the actual significance of scarcity. Polanyi shows that the classical oppositions between liberty and equality, economy and democracy can be overcame in the frame of a brand new society in which the institutional line between economics and politics should be abolished. This is sustained by an aristotelism that takes into account the social breaks produced by machinism and fascisms.
Economics; Sociology
Keywords: opulence; rareté

Propos d'Aristote sur une société d'abondance - Polanyi, Karl (Economies et sociétés, 2005)
KM: Translation of a Polanyi essay - involves Michele Cangiani and Jérôme Maucouran. Nous publions ci-dessous la traduction en français d'un texte inédit de Karl Polanyi : « Aristotle on an affluent society » (13 mars 1959, Archives de l'Institut Karl Polanyi d'économie politique, Montréal). Ce texte doit paraître aux Éditions du Seuil, en 2006, dans un recueil intitulé Essais de Karl Polanyi, sous la direction scientifique de Michele Cangiani et Jérôme Maucourant, dans la collection « Économie humaine » dirigée par Jacques Généreux. La version présente de ce texte a été traduite par Laurence Collaud en collaboration avec Michele Cangiani, Jérôme Maucourant et Christel Vivel. Œconomia remercie les Éditions du Seuil ainsi que Jacques Généreux d'avoir autorisé cette publication. We publish the French translation of an unpublished text by Karl Polanyi: "Aristotle on an affluent society" (March 13, 1959, Archives of the Karl Polanyi Institute of Political Economy, Montreal). This text is to be published by Éditions du Seuil in 2006 in a collection entitled Essays by Karl Polanyi, under the scientific direction of Michele Cangiani and Jérôme Maucourant, in the collection "Économie humaine" directed by Jacques Généreux. The present version of this text has been translated by Laurence Collaud in collaboration with Michele Cangiani, Jérôme Maucourant and Christel Vivel. Œconomia thanks Editions du Seuil and Jacques Généreux for authorizing this publication.
N/A
Keywords: ARISTOTLE; CANGIANI; Michele; MAUCOURANT; Jérôme; translation

Dé-penser l'économique sans Mauss et avec Polanyi - Sobel, Richard (L'Homme & la société, 2005)
Political Science
Keywords: MAUSS; Marcel; 1872-1950

Avec Mauss et Polanyi, vers une théorie de l'économie plurielle - Laville, Jean-Louis (Revue du MAUSS, 2003)
Mauss and Polanyi sketched the theoretical foundations of a pluralist approach to the economy and began a reflection on social change that was not satisfied with the ritual evocation of a reversal of the system. In other words, instead of an abstract call to an alternative economy, the concrete path of "altereconomies" opens the field of possibilities.
Sociology; Economics
Keywords: altereconomies

Le bénévolat dans une approche substantive de l'économie, Abstract - Gardin, Laurent (Revue française des affaires sociales, 2002)
RésuméDifférents travaux ont délivré des méthodologies et des données quantifiant l’apport du bénévolat en temps et en argent. Ces préoccupations amènent, dans le sillage des travaux de Karl Polanyi, à appréhender l’économie de manière substantive comme la dépendance de l’homme par rapport à la nature et à ses semblables. Une telle analyse montre qu’il n’y a pas nécessairement une concurrence entre ces différents registres économiques mais qu’une hybridation des ressources peut se mettre en place au service des projets associatifs. Si le bénévolat permet aux pouvoirs publics de faire des économies pour le développement de ces services, il permet aussi de développer des services plus en adéquation avec les demandes sociales, et conduit à une évolution des politiques publiques et à un déploiement de leurs actions pouvant conduire, paradoxalement, à une croissance des dépenses publiques. À partir d’exemples étudiés dans le champ de l’aide aux personnes âgées et handicapées, cette contribution vise à donner les éléments permettant la valorisation du bénévolat, à dresser une typologie des fonctions remplies par le bénévolat et à mesurer son influence sur les différents registres économiques et notamment la redistribution., Various studies have provided methodologies and data for quantifying the contribution of voluntary service in both time and money terms. This work causes one, in the wake of the work by Karl Polanyi, to apprehend the economy in substantive terms – along with the dependence of man compared to nature and his fellow creatures. Such an analysis shows that there is not necessarily a competition between these various economical registers, but that a “hybridization” of resources can be set up in the service of associative projects. If voluntary service makes it possible for the public authorities to make savings when developing such services, it also makes it possible to develop services more in line with social needs, which leads to changes in public policies and to a deployment of their actions, which can lead, paradoxically, to increased public expenditure. This article thus aims to understand the influence of voluntary service on the various economical registers, and in particular on redistribution from examples studied in the field of the assistance to the old and handicapped people, this contribution aims giving the elements allowing the valorization of the voluntary help, drawing up a typology of functions filled by the voluntary help and at measuring its influence on the various economic registers and in particular the redistribution.
Sociology; Economics
Keywords: substantiveness; voluntary service

Proximité spatiale et relations science - industrie : savoirs tacites ou encastrement (Polanyi ou Polanyi) ?, Spatial proximity and relations between academic research and firms : tacit knowledge or embeddedness (Polanyi or Polanyi) ? - Grossetti, Michel; Bès, Marie-Pierre (Revue d’Économie Régionale & Urbaine, 2002)
RésuméLes notions d’encastrement et de savoirs tacites sont souvent utilisées dans des théories expliquant les effets de proximité spatiale dans les relations entre la recherche académique et les entreprises. Même si elles ont des origines proches (ne serait-ce que parce qu’elles ont été formulées à l’origine par deux frères, Karl et Michael POLANYI), elles ont des implications très différentes en ce qui concerne l’interprétation des effets de proximité. Dans un cas (l’encastrement), on peut généraliser l’explication aux effets de proximité dans les relations entre organisations alors que dans l’autre cas (savoirs tacites), l’explication se restreint aux échanges en matière de connaissance. L’analyse d’un corpus de cas de collaboration entre les laboratoires du CNRS et les entreprises plaide en faveur de la thèse de l’encastrement., ENG: The notions of embeddedness and tacit knowledge are often used in the theories explaining spatial proximity effects in the relations between academic research and firms. Even if the two notions have a close origin (they have been defined by two brothers, Karl and Michael POLANYI), they imply different views on spatial proximity effects. In one case (embeddedness), it is possible to generalize the explanation of spatial proximity effects to all kinds of relations between organizations. In the other case (tacit knowledge), only knowledge spillovers can be explained. The analysis of a set of cooperations between firms and french academic laboratories suggests that embeddedness thesis is better.Classification JEL : O18.
Sociology
Keywords: POLANYI; Michael; 1891-1976; embeddedness; encastrement; proximité; savoirs tacites; science-industrie; tacit knowledge

Une lecture de Karl Polanyi - Maucourant, Jérôme (L'Économie politique, 2001)
Vouloir débattre de questions d’économie politique, comme la présente revue et toute l’oeuvre de Karl Polanyi (1) nous y invitent, semble relever, à l’aube du XXIe siècle, d’une absolue gageure. Sur le plan académique, l’économie politique s’est métamorphosée en une « science » économique fondée sous le double sceau de l’individualisme méthodologique et de l’affirmation d’une dichotomie totale entre faits et valeurs. A l’inverse, l’anthropologie de Polanyi se fonde sur un socialisme humaniste qui fut nourri par des lectures de Karl Marx et un ancien projet de « sociologie chrétienne ». Sur le plan théorique et politique, Karl Polanyi cherche à justifier une conception de la démocratie comme contrôle social de notre devenir. Dès 1922, chose qui est peu soulignée, il tente de penser un modèle de socialisme décentralisé pour répondre à ce qu’il considère comme l’impasse du libéralisme et l’erreur que constitue la planification centralisée.
Economics; Political Science

Le travail, la servitude et la vie. Avant Marx et Polanyi, Eugène - Vatin, François (Revue du MAUSS, 2001)
Sociology
Keywords: France; MARX; Karl; 1818-1883; history; labour

Pourquoi relire Karl Polanyi au XXIe siècle ? - Morvan-Roux, Solène; Servet, Jean-Michel; Tiran, André (L'Économie politique, 2022)
Karl Polanyi (1886-1964) est surtout connu pour son livre The Great Transformation, et en particulier pour une idée contenue dans celui-ci : la distinction entre une « économie intégrée dans les relations sociales » et « des relations sociales intégrées dans le système économique ». Selon cet auteur, les activités économiques et techniques n’étaient d’abord qu’une des nombreuses excroissances des activités humaines. L’économie archaïque a donc été au service des besoins humains. Mais, au fil du temps, influencés par la science économique dominante, les décideurs politiques ont acquis la conviction que les marchés se régulaient d’eux-mêmes pour autant que les lois et les règlements ne les en empêchent. Peu à peu, à mesure que la pensée fondée sur le libre marché s’étendait à l’ensemble de la société tout comme le règne de la machine, les humains et la nature ont été considérés comme des marchandises appelées « travail » pour ceux-ci et « terre » ou « ressources naturelles » pour celle-là. L’« économie de marché » avait transformé la société humaine en une « société de marché ». La finance et la monnaie ont joué un rôle généralement sous-estimé dans cette transformation ; un rôle que Karl Polanyi a particulièrement mis en avant et qui résonne quasi quotidiennement avec notre actualité.
Sociology; Political Science
Keywords: Great Transformation; The (Book); interdisciplinary research; market society

Penser les bouleversements du monde à partir de Karl Polanyi - Postel, Nicolas (Revue Française de Socio-Économie, 2022)
Sociology

Karl Polanyi contre Ludwig von Mises - Pinault, Santiago (Austriaca. Cahiers universitaires dʼinformation sur lʼAutriche, 2020)
Les analyses de Felix Schafer, alors le plus proche collaborateur de Karl Polanyi (1886-1964), permettent de comprendre un débat entamé en 1922 à Vienne entre Polanyi et Ludwig von Mises (qui était alors le représentant le plus célèbre de l’école autrichienne). Les enjeux de leur opposition devaient structurer la pensée polanyienne en son entier. Dans les décennies suivantes, notamment les années 1940-1950 aux États-Unis, c’est en esquissant une approche de type sociologique que Polanyi allait paradoxalement élaborer, sur des catégories conjointes qu’il tire indissociablement de Max Weber et de Carl Menger, un paradigme que nous qualifions de « vieux (ou vétéro)-autrichien » en raison de son retour aux sources de cette tradition (prise au sens large). Le formalisme de Mises s’y intègre pour former une « branche formaliste » selon Polanyi, qui nous a peut-être laissé là sa plus féconde intuition.
Economics
Keywords: Austria; MISES; Ludwig von; WEBER; Max; 1864-1920; substantivisme